(untitled) (Zien Journal of Social Sciences and Humanities, 2022)
This article provides a detailed analysis of the interaction of higher education institutions with prestigious foreign higher education institutions in Surkhandarya region during the years of independence, in particular, the history of joint educational programs and joint projects on the example of Temiz State University and Denau Institute of Entrepreneurship and Pedagogy. Made